Single dose escalation studies with inhaled POL6014, a potent novel selective reversible inhibitor of human neutrophil elastase, in healthy volunteers and subjects with cystic fibrosis - Barth, P.; Bruijnzeel, P.; Wach, A.; Sellier Kessler, O.; Hooftman, L.; Zimmermann, J.; Naue, N.; Huber, B.; Heimbeck, I.; Kappeler, D.; Timmer, W.; Chevalier, E. (Journal of cystic fibrosis, 2020)
POL6014 is a novel, orally inhaled neutrophil elastase (NE) inhibitor in development for cystic fibrosis (CF). Two studies, one in healthy volunteers (HVs, doses 20 to 960 mg) and one in subjects with CF (doses 80 to 320 mg) were conducted to evaluate the safety, tolerability and pharmacokinetics (PK) of single ascending doses of inhaled POL6014 with a Pari eFlow® nebuliser. PK was evaluated over a period of 24 h. In addition, NE activity in CF sputum was measured. After single doses, POL6014 was safe and well tolerated up to 480 mg in HVs and at all doses in subjects with CF. POL6014 showed a dose-linear PK profile in both populations with Cmax between 0.2 and 2.5 μM in HVs and between 0.2 and 0.5 μM in subjects with CF. Tmax was reached at approximately 2–3 h. Mean POL6014 levels in CF sputum rapidly reached 1000 μM and were still above 10 μM at 24 h. >1-log reduction of active NE was observed at 3 h after dosing. Inhalation of POL6014 can safely lead to high concentrations within the lung and simultaneously low plasma concentrations, allowing for a clear inhibition of NE in the sputum of subjects with CF after single dosing. Trial Registration: European Medicines Agency EudraCT-Nr. 2015-001618-83 and 2016-000493-38. •POL6014 is a new orally inhaled potent and selective neutrophil elastase inhibitor.•POL6014 is well tolerated up to 480 mg in HVs and up to 320 mg in CF subjects.•POL6014 shows a low systemic burden in comparison to orally administered drugs.•Ratio between POL6014 sputum and plasma concentrations is 1000-fold in CF subjects.•>1-log reduction of active NE in sputum is reached 3 h post dosing.